Rules of calculating pensions for soldiers on duty during war or in war zones – contribution to debate - Damian Walczak; Michał Ziemiak (Prawo Budżetowe Państwa i Samorządu, 2018)
The basis for considerations included in this article – which is designed to trigger a discussion on rules of calculating soldiers’ pensions – is the judgement of February 16, 2018 of the District Court in Łódź (VIII U 2407/17). The court ruled that for the purpose of calculating soldiers’ pension, each part of the service of soldiers who served during the war or in the war zone should be recalculated into months. Judges decided that summing individual separate periods of service calculated in days and recalculating them in full months is inconsistent with the law. The judgement of February 16, 2018 depicts well discrepancies in practice of courts and the Army Pension Bureaus. Moreover, that decision relates to the problem of the compatibility of the secondary legislation with the 1993 act on professional soldiers and their families pensions act.